Detection and transfer of antimicrobial resistance gene integron in Salmonella Enteritidis derived from avian material - Okamoto, AS [UNESP] (2009)
The expansion of global poultry production has increased the need to reduce or control the agents responsible for economic losses, including Salmonella spp. These bacteria are also of public health concern due to their potential to cause food poisoning, and, more recently, due to the antimicrobial resistance presented by these bacteria. Molecular biology is an important tool currently used in the diagnosis and research studies of main poultry diseases. The present studied analyzed 100 samples of Salmonella Enteritidis (SE) isolated from avian material aiming at detecting the class 1 integron gene, Integroninvolved in antimicrobial resistance, by means of polymerase chain reaction (PCR), and comparing it with plate inhibition test. Subsequently, SE samples were evaluated for their capacity to horizontally transfer this gene. There was no direct relationship between the presence of the class 1 integron gene and SE resistance to the 14 antimicrobials tested, as 80% of the studied samples were resistant to up to three antimicrobials, and did not present the aforementioned gene. However, horizontal transfer of this gene was accomplished in vitro (from Escherichia coli to Salmonella Enteritidis), demonstrating that capacity class 1 integron gene can be disseminated among enterobacteria.